Efficacy of extracellular vesicles as a cell-free therapy in colitis: a systematic review and meta-analysis of animal studies - Hou, Jun-Jie; Li, Wei-Wei; Wang, Xiao-Li; Ma, A-Huo; Qin, Yue-Hua (Frontiers in Pharmacology, 2023)
Extracellular vesicles (EVs) mediate inflammation, immune responses, gut barrier integrity, and intestinal homeostasis. Recently, the application of EVs in the treatment of inflammatory bowel disease (IBD) has been under intensive focus. Some studies have been conducted in the animal models of colitis, while systematic reviews and meta-analyses are lacking. The current study aimed to conduct a systematic review and meta-analysis of studies investigating the efficacy of EVs on IBD. Methods A systematic retrieval of all studies in PubMed, EMBASE, MEDLINE, Web of Science, and Cochrane Library reported the effects of EVs in the colitis model up to June 22, 2023. The methodological quality was assessed based on SYRCLE's risk of bias (RoB) tool. Disease activity index (DAI), myeloperoxidase activity (MPO), histopathological score (HS), and inflammatory cytokines (TNF-α, NF-κB, IL-1β, IL-6, and IL-10) were extracted as analysis indicators by Web Plot Digitizer 4.5. A meta-analysis was performed to calculate the standardized mean difference and 95% confidence interval using random-effect models by Review Manager 5.3 and STATA 14.0 software.A total of 21 studies were included in this meta-analysis. Although the heterogeneity between studies and the potential publication bias limits confidence in the extent of the benefit, EVs treatment was superior to the control in the colitis evaluation with reduced DAI, HS, MPO activity, and pro-inflammatory cytokines, including TNF-α, NF-κB, IL-1β, and IL-6, while increasing the content of anti-inflammatory cytokine IL-10 (all p < 0.05).Our meta-analysis results supported the protective effect of EVs on colitis rodent models based on their potential role in IBD therapy and propelling the field toward clinical studies.